Impact of probiotic-supplemented water on the performance and physiological responses of broilers under normal and heat stress conditions - Rahaf Istiteh; Mohannad Abuajamieh; Mohmmad Al-Qaisi; Mohamed A. Abedal-Majed; Anas Abdelqader (Veterinary World)
Background and Aim: Heat stress (HS) significantly compromises broiler performance, intestinal health, and immune responses, posing a growing threat under climate change. Probiotics (PROs) have been proposed as a nutritional intervention to mitigate HS effects, yet their efficacy through drinking water remains understudied. This study aimed to evaluate the effects of water-supplemented PROs on growth performance, physiological responses, intestinal morphology, and inflammatory biomarkers in broiler chickens under thermo-neutral (TN) and HS conditions.